Existence of Traveling Wave Fronts for a Generalized Nonlinear Schrodinger Equation - Yuanhua Lin; Liping He (Advances in Mathematical Physics, 2022)
In the presented paper, a generalized nonlinear Schrodinger equation without delay convolution kernel and with special delay convolution kernel is investigated. By using the geometric singular perturbation theory, the existence of traveling wave fronts is proved. Firstly, we show that such traveling wave fronts exist without delay by non-Hamiltonian qualitative analysis. Then, for the generalized nonlinear Schrodinger equation with a special local strong delay convolution kernel, the desired heteroclinic orbit is obtained by using the Fredholm theory.